Kajian Sosioteknologi Dalam Perspektif Pendidikan Kewarganegaraan: Citizenship Competence, Citizenship Education, Sociotechnology, Technology, Information and Communication, Civic Virtue. - Nanggala, Agil (Penerbit STKIP PGRI Bangkalan, 2022)
This research was conducted to develop Civics science, especially at the level of using technology, information and communication, so that it is positively beneficial for the nation's civilization and the progress of social life in society, as well as to make Civics science more holistic to address the nation's increasingly dynamic and complex problems. So that the development focuses on analysis as well as reflection on socio-technological studies in the perspective of Civics, which leads to optimal community empowerment through the use of advances in technology, information and communication intelligently, wisely and morally. This research was carried out through a qualitative approach with a literature study method, data analysis focused on: reduction, display and verification or drawing conclusions. The result of the research is that socio-technology studies in the perspective of Civics are able to strengthen civic knowledge, civic skills as well as the civic disposition of citizens that lead to civic virtue, especially in optimizing the existence of technology, information and communication, so that it has a real impact on the progress of social life, because it accommodates civic empowerment and civic movement in utilizing advances in technology, information and communication intelligently, wisely and morally, as social capital to create a civil society based on Pancasila as well as the 1945 Constitution.